DEGRADASI KARBON, NITROGEN, DAN FOSFOR TANAH PASCA KEBAKARAN LAHAN DI KEBUN KELAPA SAWIT, PROVINSI LAMPUNG - Renaldi Sambo Eka Saputra; Syahrul Kurniawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Agricultural practices, especially land clearing by burning in peat-land, usually causes land-fire and result in nutrient degradation of peat-land. The research was aimed to assess nutrient content (i.e. C, N, P) in oil palm plantation within peatlands post land fire. The study was conducted on Tulang Bawang regency, Lampung Province. Soil samples were collected from two locations with different intensity of land fire, i.e. field with low intensity of land fire (land A) and land with high intensity of land fire (land B). In each land, the soil was taken from two depths (i.e. 0-10 cm and 10-30 cm) in three different zones of oil palm plantation, named as fertilization area, frond stack, and harvested path, with three replications of each. The variable measured including soil organic C, total N, and available P. Prior to statistical analysis, the data were tested normality. The result showed that the location with low intensity of land fire (land A) had higher soil organic C, total N, and available P at 0-10 cm and 10-30 cm depths of soil as compared to the area with high land fire intensity (land B). Application of N fertilizer and liming resulted in a higher total N at 0-10 cm depth of soil and available P (in the land A) in fertilization area as compared to frond stack and harvest path areas, both in land A and land B. Available P in land B at 0-10 cm and 10-30 cm soil depth in the fertilization area was lower than harvest path and frond stack areas, and this was probably due to the high losses through leaching and/or uptake by palm oil.